Quick and easy low-cal vegan comfort food : 150 down-home recipes packed with flavor--not calories - Simpson, Alicia C. (Experiment, 2011)
"150 comforting, uncomplicated, calorie-conscious recipes featuring a wide range of vegan dishes, each with 350 calories or fewer per serving and complete nutritional data"--